2005
DOI: 10.2134/agronj2005.0011
|View full text |Cite
|
Sign up to set email alerts
|

Development of Near Infrared Reflectance Spectroscopy Calibrations to Estimate Legume Content of Multispecies Legume–Grass Mixtures

Abstract: At a low level of N supply, the proportion of N derived from atmosphere is expected to be close to 100% if the Legume content in legume-grass mixtures is a key parameter for legumes are grown in mixtures with nonlegumes. Then, the quantification of N 2 fixation, forage, and diet quality. This study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 16 publications
0
31
1
1
Order By: Relevance
“…In this study, 132 sample spectra were set aside as external, independent validation set, which was not included in either of the calibration and test validation, but contained, at least in part, some of the original pure root material. Most studies have shown that crossvalidation provides slightly superior predictive performance to external test validation (Locher et al 2005a;Martens and Dardenne 1998;Moron and Cozzolino 2004). However, in the present study, Model 1, which was based on cross-validation for the whole dataset, was not superior with respect to the RMSECV or RMSEP and r 2 when compared to Model 2 and Model 3, which were developed through validation against external test sets following calibration.…”
Section: Model Development and Validationcontrasting
confidence: 72%
See 1 more Smart Citation
“…In this study, 132 sample spectra were set aside as external, independent validation set, which was not included in either of the calibration and test validation, but contained, at least in part, some of the original pure root material. Most studies have shown that crossvalidation provides slightly superior predictive performance to external test validation (Locher et al 2005a;Martens and Dardenne 1998;Moron and Cozzolino 2004). However, in the present study, Model 1, which was based on cross-validation for the whole dataset, was not superior with respect to the RMSECV or RMSEP and r 2 when compared to Model 2 and Model 3, which were developed through validation against external test sets following calibration.…”
Section: Model Development and Validationcontrasting
confidence: 72%
“…Near infrared reflectance spectroscopy (NIRS) is a rapid non-destructive technique with the capacity to distinguish and quantify botanical composition in mixtures (Locher et al 2005a;Pitman et al 1991;Wachendorf et al 1999). The fact that near-infrared radiation is absorbed mainly by C-H, N-H and O-H bonds, of which organic compounds are composed, makes it particularly suitable to determine the composition of organic mixtures (Foley et al 1998;Richardson and Reeves 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, a handful of recent studies including this one demonstrate that NIRS can be applied broadly, and can include a number of different plant species in a single equation that predicts nutritional attributes(da Costa and Volery 2005;Lawler et al 2006;Locher et al 2005;Woolnough and Foley 2002),…”
mentioning
confidence: 99%
“…Grass species are likely to have similar biochemical composition, leading to similar spectral signatures. Locher et al (2005a) developed a NIRS calibration that predicted legume content based on artificial sample mixtures containing a range of legumes and grasses from one farm in Germany. Locher et al (2005a) developed a NIRS calibration that predicted legume content based on artificial sample mixtures containing a range of legumes and grasses from one farm in Germany.…”
mentioning
confidence: 99%
“…Legume proportion in mixture with multiple grass species was predicted with high accuracy (Chataigner et al, 2010). Different calibration strategies did not lead to relevant differences, and sample preparation was less important for prediction accuracy than the precision of the reference data used (Locher et al, 2005a). Different calibration strategies did not lead to relevant differences, and sample preparation was less important for prediction accuracy than the precision of the reference data used (Locher et al, 2005a).…”
mentioning
confidence: 99%